Properties of Denture Liners - A Review - Nivedha .M1 , Balaji ganesh S2 , K. R. Don3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Denture liners are the materials applied to the tissue side of a denture coming in contact with the soft tissue.It cushions the contact of the denture with the tissues. The usage of the denture liners is to alleviate thetrauma associated with complete dentures. The failure in adhesion, changes in rough surfaces and hardnessare the favourable factors for microbial accumulation and compromise the liner’s durability and causes theoral health conditions like denture stomatitis. The adhesion can be improved with the usage of differentsubstances and surface treatments. The changes in the rough surface and hardness can compromise thematerial’s lifespan. This review deals about the properties of adhesion, roughness and hardness of thedenture liners.